2020
DOI: 10.1007/s10508-019-01569-x
|View full text |Cite
|
Sign up to set email alerts
|

The Internalization of Social Stigma Among Minor-Attracted Persons: Implications for Treatment

Abstract: In this article, we sought to build on existing stigmatization research by examining the extent to which internalized stigmatization (i.e., the personal adoption and incorporation of social views, operationalized as thought suppression-an avoidant coping strategy-and low psychological well-being) among minor-attracted persons (MAPs) may impact upon help-seeking behaviors and their avoidance of children. We adopted a cross-sectional anonymous survey design to recruit a sample of selfidentified MAPs (N = 183) fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 73 publications
4
68
0
Order By: Relevance
“…Furthermore, our results suggest various negative influences of the media coverage especially on those people with pedophilic interests who are seeking therapeutic help. This corresponds with other quantitative and qualitative studies that indicated a negative effect of public stigma on people with pedophilic interests [ 26 , 29 , 30 ], while adding important observations on how the media reporting in particular may add to this stigma. With regards to the influence of media stigmatization on the barrier to self-referring to treatment, our study provides further valuable insights.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Furthermore, our results suggest various negative influences of the media coverage especially on those people with pedophilic interests who are seeking therapeutic help. This corresponds with other quantitative and qualitative studies that indicated a negative effect of public stigma on people with pedophilic interests [ 26 , 29 , 30 ], while adding important observations on how the media reporting in particular may add to this stigma. With regards to the influence of media stigmatization on the barrier to self-referring to treatment, our study provides further valuable insights.…”
Section: Discussionsupporting
confidence: 86%
“…This kind of prevention framing may not reflect the actual needs of many non-offending people with pedophilia. According to recent studies [ 29 ], many people with pedophilic disorder are primarily looking for help to learn how to deal with psychosocial problems and psychological distress and not because they see themselves at risk of committing child sexual abuse offenses. An additional or alternative framing, which focuses on the psychological needs of the affected persons and not on child sexual abuse prevention, could inform non-offending people with pedophilia about therapeutic approaches that better suit their mental health goals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Individuals who have a sexual attraction to minors face vast amounts of social stigma (Jahnke et al, 2015a) and experience stress and mental ill health as a result of this (Jahnke et al, 2015b;Lievesley et al, 2020). These issues can have profound effects on MAPs' willingness and ability to seek support for their sexual interests (Grady et al, 2018;Levenson & Grady, 2019;Levenson et al, 2017), which reduces the potential reach and impact of schemes designed to prevent the incidence of child sexual abuse.…”
Section: Introductionmentioning
confidence: 99%